Web-Based Application Of Population Services In Keboharan Village, Krian – Sidoarjo - Amwalinsanu Amwalinsanu; Hindarto Hindarto (Universitas Muhammadiyah Sidoarjo, 2022)
The resident service is obliged to provide protection and recognition of the personal status and legal status of every population event. For this reason, every important event requires every valid evidence to be administered and recorded in accordance with the provisions of the law. Population matters relating to the number of structures, gender, religion, birth, marriage, pregnancy, death, and the quality of the political economy, social, and culture. Population and important events require valid evidence for administration and recording in accordance with the provisions of the law. Population administration is defined as services in the population sector provided by government and non-government officials from the central level to the village or sub-district level, RW and RT. In population administration services, government and non-government officials provide services such as arranging marriage permits, applying for ID cards, certificates, and family cards, and other residence documents.